Studies on Stress Relief Heat Treatment of 316L Stainless Steel in Wire Arc Additive Manufacturing using Simufact Welding Simulation - CHE BAHARUM, CHE MUHAMMAD NAJMI; ASMAWI, ROSLI; Mohd Halim Irwan Ibrahim; Sarah Nadiah Mohd Ghazali (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Wire Arc Additive Manufacturing (WAAM) is gaining recognition in various industries for producing large scale metal components, but the high heat input during the process causes significant residual stress, compromising the mechanical properties and reliability of the final product. This study focuses on mitigating these stresses by developing a numerical simulation model to optimize stress relief heat treatment (SRHT) for 316L steel WAAM components. It begins with an introduction to WAAM's industrial significance and challenges, followed by a literature review on residual stress causes, existing SRHT techniques, and numerical modelling. The methodology includes designing a simulation model, optimizing SRHT parameters using Simufact Welding software, and validating the results through experimental comparisons. The findings highlight the model's effectiveness in reducing residual stress and improving mechanical properties, showcasing how advanced simulation techniques enhance WAAM technology and offer practical solutions for industrial applications and future research involving diverse materials and geometries.